Binding and/or hydrolysis of purine‐based nucleotides is not required for IM30 ring formation. Issue 14 (21st June 2021) - Siebenaller, Carmen; Schlösser, Lukas; Junglas, Benedikt; Schmidt‐Dengler, Martina; Jacob, Dominik; Hellmann, Nadja; Sachse, Carsten; Helm, Mark; Schneider, Dirk
Abstract : IM30, the inner membrane‐associated protein of 30 kDa, is conserved in cyanobacteria and chloroplasts. Although its exact physiological function is still mysterious, IM30 is clearly essential for thylakoid membrane biogenesis and/or dynamics. Recently, a cryptic IM30 GTPase activity has been reported, albeit thus far no physiological function has been attributed to this. Yet, it is still possible that GTP binding/hydrolysis affects formation of the prototypical large homo‐oligomeric IM30 ring and rod structures. Here, we show that the Synechocystis sp. PCC 6803 IM30 protein in fact is an NTPase that hydrolyzes GTP and ATP, but not CTP or UTP, with about identical rates. While IM30 forms large oligomeric ring complexes, nucleotide binding and/or hydrolysis are clearly not required for ring formation. Abstract :